Exploring the viral world through metagenomics - Rosario, Karyna; Breitbart, Mya (Current opinion in virology, 2011)
► Viral metagenomics provides fundamental insights into viral ecology and evolution. ► Environmental viromes encompass vast genetic diversity that is largely unknown. ► CRISPRs can link viruses to uncultured hosts and provide a history of viral exposure. ► Viruses contain diverse auxiliary metabolic genes that may affect host function. ► Viral metagenomics enhances pathogen surveillance and biotechnology efforts. Viral metagenomics, or shotgun sequencing of purified viral particles, has revolutionized the field of environmental virology by allowing the exploration of viral communities in a variety of sample types throughout the biosphere. The introduction of viral metagenomics has demonstrated that dominant viruses in environmental communities are not well-represented by the cultured viruses in existing sequence databases. Viral metagenomic studies have provided insights into viral ecology by elucidating the genetic potential, community structure, and biogeography of environmental viruses. In addition, viral metagenomics has expanded current knowledge of virus–host interactions by uncovering genes that may allow viruses to manipulate their hosts in unexpected ways. The intrinsic potential for virus discovery through viral metagenomics can help advance a wide array of disciplines including evolutionary biology, pathogen surveillance, and biotechnology.